Gamification and gaming proposals, teachers’ perceptions and practices in Primary Education - José Manuel Sáez-López; Esteban Vázquez-Cano; Javier Fombona Cadavieco; Eloy López-Meneses (Interaction Design and Architecture(s), 2022)
This research has analyzed the application of gamification and game-based learning to primary education based on the evaluation of gamification by 308 primary education teachers in Spain. A quantitative and qualitative analysis was made of teachers’ competences, the tools and devices most widely used, didactic functionality, emotional competence and social skills. The results showed that teachers had a positive attitude towards gamification, and good knowledge and management of tools such as Genially, Kahoot and Google Classroom. With the appropriate resources, class planning and teacher training, game-based learning and gamification can boost student motivation and commitment, and foster enthusiasm for beneficial, pedagogical interactive processes.